Measurement correlation in a target tracking system using range and bearing observations - Pistorius, Morne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Mathematical Sciences. Applied Mathematics))--University of Stellenbosch, 2006.